THREE DIMENSIONAL STRESSES IN ICEBREAKER PRIMARY STRUCTURES. - Genalis,Paris (1967)
The validity of the current design practice of selection of icebreaker primary structure scantlings on the basis of two dimensional analyses is examined by comparing the results of a two dimensional analysis with the results of three analyses of more than one frame connected by longitudinal members. Bending moments, and axial and shear forces are calculated at the ends of each member of the truss structure. Deflections and rotations of each end of each member and deflections and rotations of each free joint are included. All analyses have been performed using the stiffness matrix method as utilized by the current version of the STRESS computer program. Through the use of this program, its applicability to two and three dimensional analyses (of icebreaking vessel's primary structure and ship's framing analyses, in general) is examined. (Author)